Performance of chromium nitride based coatings under plastic processing conditions - Cunha, L. (2000)
Chromium nitride based coatings were produced in the form of monolithic and multilayer coatings, by DC and RF reactive magnetron sputtering. These coatings were deposited onto stainless steel and tool steel substrates. Chromium nitride coatings have;proved to be wear and corrosion resistant. The combination of these characteristics was necessary to protect surfaces during plastic processing. In order to select the best coatings, some mechanical and tribological tests were performed. Hardness and Young's modulus of the produced coatings were measured by nano-indentation, adhesion was assessed by scratch test experiments and wear was evaluated by performing pin-on-disc experiments. The behaviour of these coatings in chemically aggressive environments was studied by different corrosion experiments. The behaviour of these coatings in thermoplastic processing equipment was also studied. The abrasive and corrosive wear of chromium nitride based coatings was assessedu nder relatively high pressures and temperatures and was compared with the surface wear of hardened tool steel substrate by heat treatment, nitrided by chemical-heat treatment, or protected by hard chromium coating deposited in a galvanic way. Monolithic coatings were harder, and had higher Young modulus and adhesion when compared with multilayered coatings. Their wear resistance, measured by pin-on-disc test, was between two and three orders of magnitude higher, but multilayer coatings showed significantly better corrosion resistance. In general, monolithic and multilayer coatings have significantly better behaviour when compared with traditional processes of protecting functional surfaces for plastic transformation equipment. The measured wear of the bcst performance obtained by chromium nitride based coatings can be more than two orders of magnitude lower than nitrided surfaces or hard chromium coated samples.